Freedom songs : a tale of the Underground Railroad - Robbins, Trina (Stone Arch Books, 2008)
Sarah, a fourteen-year-old slave living in Maryland in the 1850s, tries to escape to freedom in the North through the Underground Railroad, knowing that her path to freedom will be filled with danger.